A new hydroxyapatite-alginate-gelatin biocomposite favor bone regeneration in a critical-sized calvarial defect model - Santos, Anderson Cunha Dos; Aroni, Mauricio Andres Tinajero [UNESP]; Pigossi, Suzane Cristina; Lopes, Maria Eduarda Scordamaia [UNESP]; Cerri, Paulo Sergio [UNESP]; Miguel, Fúlvio Borges; Santos, Silvia Rachel de Albuquerque; Cirelli, Joni Augusto [UNESP]; Rosa, Fabiana Paim (FapUNIFESP (SciELO), 2024)
This study aimed to evaluate the osteogenic potential of hydroxyapatite (HA), Alginate (Alg), and Gelatine (Gel) composite in a critical-size defect model in rats. Twenty-four male rats were divided into three groups: a negative control with no treatment (Control group), a positive control treated with deproteinized bovine bone mineral (DBBM group), and the experimental group treated with the new HA-Alg-Gel composite (HA-Alg-Gel group). A critical size defect (8.5mm) was made in the rat's calvaria, and the bone formation was evaluated by in vivo microcomputed tomography analysis (µCT) after 1, 15, 45, and 90 days. After 90 days, the animals were euthanized and histological and histomorphometric analyses were performed. A higher proportion of mineralized tissue/biomaterial was observed in the DBBM group when compared to the HA-Alg-Gel and Control groups in the µCT analysis during all analysis periods. However, no differences were observed in the mineralized tissue/biomaterial proportion observed on day 1 (immediate postoperative) in comparison to later periods of analysis in all groups. In the histomorphometric analysis, the HA-Alg-Gel and Control groups showed higher bone formation than the DBBM group. Moreover, in histological analysis, five samples of the HA-Alg-Gal group exhibited formed bone spicules adjacent to the graft granules against only two of eight samples in the DBBM group. Both graft materials ensured the maintenance of defect bone thickness, while a tissue thickness reduction was observed in the control group. In conclusion, this study demonstrated the osteoconductive potential of HA-Alg-Gel bone graft by supporting new bone formation around its particles.
Keywords: alginates; bone regeneration; hydroxyapatite